Improving the oscillating wind turbine model - Shtanko, Oleksandr; Litvinova, Maryna; Zorina, Iryna; Karpova, Svitlana; Avdiunin, Roman (Eastern-European Journal of Enterprise Technologies, 2023)
Disadvantages in the structure of the most common rotary wind generators limit their use. This motivates the development of alternative types of wind turbines, the most promising of which are oscillating wind generators. The object of the study is the structure of an oscillating type wind generator, which provides self-oscillating movement of the blade-wing. The design of the wind generator uses a modified wing shape to provide maximum lift. For this purpose, added elements are the tip and flap, which affect the shape of the wing, its angle of attack, and regulate the direction of the lifting force. The principle of attaching the tip and flap to the wing using spiral springs has been developed. The structure also includes locking magnets that affect the movement of the wing during a turn. The mechanism that drives the self-oscillating mode of operation of the wind turbine was described. This mode occurs under the action of the inertial force of the movement of the wing, the force of elasticity, the repulsive force of the magnets, and the pressure force of the air flow. A computer simulation of the wind generator was carried out using the Ansys CFX software package. The model of the flow around an absolutely rigid body at small values of the Reynolds number was applied. The resulting dynamics of the horizontal movement of the wing of the wind turbine make it possible to use it for energy generation already at a wind speed of 2 m/s. The low cost of the wing and the automatic regulation of its movement make it possible to install many wings to increase the power of the wind generator. Thus, the improved wind turbine is low-cost, harmless to birds, has self-regulation of wing movement and can use the low-speed component of the wind, which significantly expands the geography of its operation. It is possible to transfer the proposed technological solutions for the construction of hydroelectric generators